United we stand? Survey results on the views of French, German and Italian parliamentarians on EU and EMU reforms - Sebastian Blesse; Massimo Bordignon; Pierre C. Boyer; Piergiorgio Carapella; Friedrich Heinemann; Eckhard Janeba; Anasuya Raj (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
The "multicrisis" of European integration from the euro debt crisis through the migration dispute to Brexit has kicked-off a comprehensive reform debate. This debate covers the evolution of European Monetary Union (EMU) institutions, the division of competencies between the EU and Member States, and reforms to the decision making and financing of the EU. While there is a wealth of innovative ideas across all these dimensions, the hurdles for a far-reaching reform are high, as they require a consensus among veto players. In this policy brief, we document descriptive insights of a unique recent survey among the national parliaments of the three largest Member States of the post-Brexit EU: France, Germany and Italy. Any far-reaching EMU or EU reform will have to be approved by the national parliaments of Member States. A consensus between these three countries is definitely not a sufficient condition for the political feasibility of a reform but most likely it amounts to a necessary one. The survey on the future of European integration was conducted in the national parliaments of France, Germany and Italy, including the French Senate and Assemblée Nationale, the German Bundestag, and the Italian Camera dei Deputati and Senato della Repubblica. The survey was sent out in September 2018 and responses arrived until January 2019. It covers the three mentioned reform dimensions, i.e. the division of competencies between the European and national level, EMU reforms and the future of EU finance and decision making. – – Der europäische Integrationsprozess wird gleich von mehreren Krisen erschüttert - der Euro-Schuldenkrise, der Flüchtlingsfrage und dem Brexit-Konflikt - , was eine umfassende Reform-Debatte ausgelöst hat. Bei dieser Debatte geht es sowohl um die Entwicklung der Institutionen der Europäischen Währungsunion (WWU), die Aufteilung von Kompetenzen zwischen der EU und den Mitgliedstaaten als auch um Reformen bezüglich der Entscheidungsfindung und der Finanzierung innerhalb der EU. Obwohl es zu all diesen Themen eine Fülle innovativer Ideen gibt, sind die Hürden für weitreichende Reformen dennoch hoch, da sie einen Konsens unter allen Veto-Mächten erfordern. Dieser Policy Brief fasst die Erkenntnisse aus einer kürzlich durchgeführten einzigartigen Umfrage zusammen, die unter den nationalen Parlamenten der drei größten Mitgliedstaaten der Post-Brexit-EU vorgenommen wurde. Jede weitreichende WWU- oder EU-Reform muss von den nationalen Parlamenten der Mitgliedsstaaten genehmigt werden. Ein Konsens unter diesen drei Ländern ist daher eine notwendige Bedingung für die politische Umsetzbarkeit einer solchen Reform. Die Umfrage zur Zukunft der europäischen Integration wurde in den nationalen Parlamenten in Frankreich, Deutschland und Italien durchgeführt, darunter in der französischen Nationalversammlung und im Sénat, im Deutschen Bundestag sowie in der italienischen Camera dei deputati und dem Senato della Repubblica. Die Umfrage lief von September 2018 bis Januar 2019. Sie umfasst die drei genannten Reformdimensionen, d.h. die Aufteilung der Zuständigkeiten zwischen der europäischen und der nationalen Ebene, WWU-Reformen und die Zukunft der Finanzierung und Entscheidungsfindung innerhalb der EU.
Keywords: 330